Language choice, language alternation and code-switching in the Mercator-Hondius Atlas - Mäkilähde, Aleksi (Approaching Religion, 2016)
The atlas of Gerardus Mercator (Gerard de Cremer), or the Atlas sive cosmographicae meditationes de fabrica mundi et fabricati figura, is one of first modern atlases and one of the most famous of those compiled in the Netherlands. The first (unfinished) edition was published in 1595, but the copperplates were later acquired by Jodocus Hondius (Joost de Hondt) and his business associates. The revised Mercator-Hondius Atlas was published for the first time in 1606 with added maps and texts. The texts printed on verso of the maps were written by Petrus Montanus (Pieter van den Berg), who was a brother-in-law of Hondius and a Latin teacher. Many subsequent editions of the atlas were produced in the years that followed. The first editions were in Latin, but versions in European vernaculars such as French, German and Italian were produced later as well. The present article focuses on the multilingual nature of the Mercator-Hondius Atlas (1613, editio quarta) by discussing language choice, language alternation and code-switching patterns in different parts of the atlas. The dominant language of the descriptive texts is Latin, but there are also switches into many other languages, including Greek (written in Greek script) and several vernaculars. Furthermore, the map pages tend to indicate the names of different types of area (e.g. cities, seas, and oceans) in different languages. The aim of the present article is to provide a preliminary exploration of the possibilities of approaching the atlas with the aid of concepts and ideas derived from modern code-switching studies. I demonstrate how these concepts can be used to describe the language choice patterns in the text and discuss some of the challenges the data poses for a linguistic approach.